2005
DOI: 10.1086/502487
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trends in Antimicrobial Susceptibilities Across Long-Term–Care Facilities: Emergence of Fluoroquinolone Resistance

Abstract: The prevalence of antimicrobial resistance has increased significantly in LTCFs, although trends have varied substantially across different institutions. These trends have been particularly pronounced for fluoroquinolone resistance among the Enterobacteriaceae. These findings demonstrate that antimicrobial resistance is widespread and increasing in LTCFs, highlighting the need for future studies to more clearly elucidate the risk factors for, and potential interventions against, emerging resistance in these se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 34 publications
(22 reference statements)
3
39
0
3
Order By: Relevance
“…However, previous review studies have reported an increasing trend in resistance to ciprofloxacin in recent years (12).…”
Section: Introductionmentioning
confidence: 95%
“…However, previous review studies have reported an increasing trend in resistance to ciprofloxacin in recent years (12).…”
Section: Introductionmentioning
confidence: 95%
“…Long-term care facilities are also emerging as major reservoirs of both antimicrobial use and bacterial resistance (25,96,156). Antimicrobial stewardship programs may fail to affect hospital resistance rates if importation of resistant organisms from the community and long-term care facilities is significant, since the programs have no control over antimicrobial use in these settings.…”
Section: Enhanced Understanding Of the Relationship Between Antimicromentioning
confidence: 99%
“…Antimicrobial resistance in enteropathogens is a public health problem that has increased in both nosocomial (14,50) and community settings (21), creating barriers to effective therapies (14). There is evidence that changes in antimicrobial use may result in a reduction in the prevalence of resistant bacteria (1,24).…”
mentioning
confidence: 99%